Brief communication: Towards disability inclusive risk management - Coutureau, Vesna; Bork-Hüffer, Tabea; Keiler, Margreth (Natural hazards and earth system sciences, 2026)
People with disabilities face heightened vulnerability during disasters, yet they remain underrepresented in risk management planning and response. This brief communication reports findings from a pilot study in Tyrol, Austria, which assessed flood exposure and disaster preparedness in facilities serving people with disabilities. Spatial analysis revealed significant exposure to flood hazards, while qualitative interviews and document analysis identified critical gaps in risk awareness, preparedness, and inclusive planning. The study underscores the urgent need for disability-inclusive disaster risk management, emphasizing accessible information, targeted preparedness measures, and the integration of disability perspectives into emergency planning to enhance resilience for all.